A Short-Term Longitudinal Investigation of the Relationship Between Trait Mindfulness and Female-Perpetrated Dating Violence. Issue 19 (October 2021) - Hesse, Calvin; Shorey, Ryan C.; Brem, Meagan J.; Stuart, Gregory L.; Cornelius, Tara L.
Within the past several decades, dating violence has emerged as a major health problem, with rates of physical violence ranging from 20% to 30% and psychological aggression ranging from 60% to 90% in college dating relationships. Despite this, there have been few successful dating violence prevention programs developed. Thus, it is imperative that research can identify the relationship between potential protective factors, such as trait mindfulness, and dating violence perpetration. This study builds upon previous research on mindfulness and dating violence by investigating this question within a sample of female undergraduate students at two universities ( N = 381) over the course of one semester. Findings suggested that the nonjudging aspect of mindfulness was associated with less perpetration of psychological and physical aggression approximately 3 months later. Furthermore, several facets of mindfulness were able to differentiate individuals who perpetrated aggression at Time 2 relative to individuals without a history of perpetration. These findings build on previous work in the field and suggest that mindfulness may play an important role in the manifestation of dating violence. Directions for future research on the relation between mindfulness and dating violence are discussed.